2019
DOI: 10.14744/ejmi.2019.41571
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Alexithymia and Depression in Patients with Multiple Sclerosis

Abstract: M ultiple Sclerosis (MS) is a chronic, progressive, demyelinating disorder of the Central Nervous System (CNS), seen mostly in young adolescents and early adulthood and it may result in physical disability. [1] Neuropsychiatric symptoms such as depression, fatigue, anxiety, cognitive impairment and alterations in personality can be seen in MS patients. They are usually seen concomitantly, and it is important to discriminate these symptoms in order to give the appropriate treatment. [1,2] Depression is the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
3
1
0
Order By: Relevance
“…It was stated that atrophy and lesions in the prefrontal cortex affecting the ventromedial and dorsolateral regions were linked to emotion processing, alexithymia, and empathy in MS patients 4. Consistent with the literature, in our study, alexithymia rates were higher in the MS patients compared with the healthy participants 8,24,26. This finding is consistent with the fact that the disease causes neurobiological damage.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It was stated that atrophy and lesions in the prefrontal cortex affecting the ventromedial and dorsolateral regions were linked to emotion processing, alexithymia, and empathy in MS patients 4. Consistent with the literature, in our study, alexithymia rates were higher in the MS patients compared with the healthy participants 8,24,26. This finding is consistent with the fact that the disease causes neurobiological damage.…”
Section: Discussionsupporting
confidence: 93%
“…Alexithymia, which is described as the lack of ability of individuals to perceive their or other people's feelings,8 is common in neurological diseases and various psychiatric disorders 23. Consistent with other publications, 41% of our sample had alexithymic symptoms 4,8,24–26. A longitudinal study based on a 5-year period suggested that the frequency of alexithymia in MS patients did not differ over time.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations